Recurrent Painful Ophthalmoplegic Neuropathy Mistaken for Oculomotor Schwannoma: A Case Report - Mahović, Darija; Bračić, Matea; Jovanović, Ivan; Gabrić, Ivo Darko (Journal of Pediatric Neurology, 2022)
Recurrent painful ophthalmoplegic neuropathy (RPON) is a headache disorder classified as a cranial neuropathy. It is characterized by episodes of unilateral headache followed by ipsilateral ophthalmoplegia due to ocular cranial nerve palsy. Symptoms usually subside spontaneously within weeks to months. RPON commonly occurs in childhood, though it is overlooked at times as a possible differential diagnosis. The pathophysiology of RPON is not entirely clear. Typical magnetic resonance imaging (MRI) findings in children include nerve thickening and gadolinium enhancement. However, these findings are not specific to this condition. Nerve thickening in RPON can resemble schwannomas, thereby causing a diagnostic dilemma. Here, we present a 13-year-old boy with a history of unilateral headaches associated with ipsilateral ptosis and diplopia. The first MRI indicated thickening and gadolinium enhancement of the right oculomotor nerve, which was interpreted as a schwannoma. However, his symptoms resolved after a few weeks and the follow-up MRI showed resolution of nerve changes. This clinical presentation was consistent with RPON. This case demonstrates the need for a careful follow-up of RPON patients.
Keywords: recurrent painful ophthalmoplegic neuropathy; headache; schwannoma; case report